Troponin T concentrations 72 hours after myocardial infarction as a serological estimate of infarct size. Issue 6 (1st June 2002) - Licka, M; Zimmermann, R; Zehelein, J; Dengler, T J; Katus, H A; Kübler, W
Abstract : Background: After acute myocardial infarction, the structural protein T is released considerably longer than cytosolic creatine kinase (CK), CK MB isoenzyme (CK-MB), or lactate dehydrogenase (LDH) and late troponin T release (> 48 hours after onset of chest pain) appears to be less affected by early coronary reperfusion. Objective: To investigate the precision of a single measurement of circulating troponin T concentrations 72 hours after onset of chest pain compared with standard scintigraphic and enzymatic estimates of myocardial infarct size. Methods: Quantitative single photon emission computed tomography thallium-201 scintigraphy at rest was performed in 37 patients 2–3 weeks after myocardial infarction (group 1: 14 patients without early coronary reperfusion; group 2: 23 patients with early reperfusion achieved by thrombolytic therapy, by percutaneous transluminal coronary angioplasty, or by both). Results: In both groups, the number of myocardial segments with abnormal thallium-201 uptake indicating the individual extent of irreversible myocardial damage correlated significantly with the troponin T concentrations 72 hours after infarction as well as with peak concentrations of CK, CK-MB, and LDH. Conclusion: The data show that a single measurement of circulating troponin T 72 hours after onset of chest pain—independent of reperfusion—is superior for the estimation of myocardial infarct size to measurement of peak CK, CK-MB, or LDH, which require serial determinations and depend on coronary reperfusion.